Penyusunan Laporan Keuangan Perusahaan Menggunakan Aplikasi Spreadsheet : (Pada PD Beras Padaringan) - Satria, Muhammad Rizal; Fatmawati, Ade Pipit (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This research is designed to create financial reports using the Spreadsheet application. The application was chosen because many companies in Indonesia, especially MSMEs, process and prepare financial reports using spreadsheets in Microsoft Excel. Many companies have used integrated computer software-based accounting applications, but they still use Spreadsheets in Microsoft Excel as initial data as well as corporate backup data. There are also many companies that still use traditional methods in financial accounting, one of which is PD Padaringan Rice. The company is still recording accounting manually, it is related to funds to buy an integrated accounting application, therefore it is necessary to make a model of the company's financial reporting work using the Spreadsheet program. This is expected to help PD Padaringan Rice and other SMEs who want to make financial reports easily, cheaply and in accordance with SAK ETAP using the Spreadsheet application in Microsoft Excel